Studies on the Flora of Kutch, Gujarat State (India) and Their Utility in the Economic Development Of The Semi- Arid Region - Rao, Rolla Seshagiri (Annals of Arid Zone, 2016)
The Flora of Kutch, Gujarat State (India) has been under study for the last few years and so far about 700 (seven hundred) species covering 95 families have bern reported. Families like Poaceae, Fabaceae, Asteraceae, Malvaceae, Euphorbiaceae, Convolvulaceae and Cyperaceae have been found to be predominant. Among these more than 70 species of grasses of (about 20 species of excellent nutritive. value) and 50 species of legumes (about 15 species of very high fodder value) form the main source of fodder in semi-arid zone of Kutch where the maximum temperature in summer is about 39Â°C and the minimum in winter lO deg C with a very scanty rainfall of 350 mm. The Banni grasslands of Kutch are renowned for cattle wealth. Forage grasses like Cenchrus ciliaris, C. setigerus. Panicum antidotale, Ohry8opogonfulvus and a few others have been found to be most nutritious, bringing about higher yield of milk when judiciously mixed up with legume species of Alysicarpus, Desmodium and Indigofera which supplement the protein defiiciency in the diet of the cattle. Proper management of grasslands by way of restricted and regulated grazing, judicious maintenance of most nutritious grass-legume combination and development of permanent land rotational pastures and also proper selection of high quality forages comprising of superior genetic strains of the indigenous species of cenchrus, Panicum and others already developed in the country, is very essential for improving the quality of cattle breed. To add to this, growth of soil stabilisers like species of Saccharum, Themeda and the cultivation of salt thriving species of Sporobolu8, Ohlori8, cenchrus and others for reclamation of saline tracts, have to be encouraged. Other natural resources like gums of Commiphora wightii and Acacia species, essential oils from Oymbopogon martinii and Vetiveria zizanioides and medicinal extracts from species of Withania. Pso,alea, Grewia, Peganum can be developed by the systematic cultivation of these species in their natural habitat. By utilising such limited plant-resources data of floristic studies and by proper planning on the various aspects suggested above, coupled with the suitable exploitation of the underground water resources, the economic standards can be satisfactorily developed.